Pengaruh corporate governance, profitabilitas, likuiditas dan solvabilitas terhadap corporate social responsibility disclosure - GAGAT AGUS WASITO; ELIADA HERWIYANTI; WIDYA HAYU WARMMESWARA KUSUMASTATI (Jurnal Bisnis dan Akuntansi, 2016)
The purpose of this research is to analyze the influence of corporate governance, profitability, liquidity and solvency on corporate social responsibility disclosure in companies listed on the Indonesia Stock Exchange. The number of data is 32 and takes from 16 sample companies in 2013 to 2014. The results of this research are as follows Corporate Governance has no effect on corporate social responsibility disclosure; Profitability has no effect on corporate social responsibility disclosure; Liquidity has a significant and positive effect on the corporate social responsibility disclosure; Solvency has a significant and negative effect on the corporate social responsibility disclosure